Factors influencing cash Waqf literacy: evidences among Gontor students - Susilo, Adib; Abdullah, Nurdianawati Irwani; Che Embi, Nor Azizan (2024)
The objective of this study is to explore the factors that influence cash waqf literacy among students at Gontor Islamic Boarding School, an institution that has implemented waqf practices since it was established as a waqf-based educational entity. A quantitative research approach was utilized, with multiple linear regression as the main method of analysis. Data were collected from 120 students at Gontor who were actively involved in a cash waqf project. The respondents were selected using simple random sampling, and SPSS software version 20 was employed to analyze the data. The results of this study indicate that education (X1), environment (X2), and cash waqf practice (X3) together influence cash waqf literacy. Specifically, education and cash waqf practice were found to have a positive and significant effect on literacy, while the environment did not show a significant impact. Furthermore, the R-squared value of the model was 0.684, meaning that approximately 68.4% of the variance in cash waqf literacy can be explained by the independent variables, while the remaining 31.6% is attributed to other factors not examined in this study. These findings highlight the crucial role of education and practice in promoting cash waqf literacy and suggest potential areas for further research.